The Effect of Cooperative Integrated Reading and Composition (CIRC) Method Through WhatsApp Application on Students’ Reading Comprehension - Hendriati Afebri; Hanna Hanna; La Ode Nggawu (Halu Oleo University, 2021)
The objectives of the research were to investigate the effect of Cooperative Integrated Reading and Composition (CIRC) technique through WhatsApp application on students’ reading comprehension and to investigate the usefulness of WhatsApp as a learning media. This study employed a quasiexperimental research design. A total of 27 participants from Senior High School 1 Tiworo Kepulauan, Muna Barat regency participated in this study. CIRC technique through WhatsApp was applied in teaching reading comprehension in the experimental group, while the control group attended conventional teaching without CIRC. Both groups learned the same materials. Pre-test was administered before treatment to examine students’ previous reading comprehension and posttest was administered immediately after the treatment. Findings of the research revealed that there was a significant effect of CIRC through WhatsApp Application on students’ reading comprehension. The gain scores of students attending CIRC were significantly higher than those of students attending conventional instruction, p = 0.002< 0.05. Results of the questionnaire suggested that WhatsApp was a useful learning media as far as the students are concerned.